If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.02(5 + -1x) = 0.03(x + 7) + -0.01 (5 * 0.02 + -1x * 0.02) = 0.03(x + 7) + -0.01 (0.1 + -0.02x) = 0.03(x + 7) + -0.01 Reorder the terms: 0.1 + -0.02x = 0.03(7 + x) + -0.01 0.1 + -0.02x = (7 * 0.03 + x * 0.03) + -0.01 0.1 + -0.02x = (0.21 + 0.03x) + -0.01 Reorder the terms: 0.1 + -0.02x = 0.21 + -0.01 + 0.03x Combine like terms: 0.21 + -0.01 = 0.2 0.1 + -0.02x = 0.2 + 0.03x Solving 0.1 + -0.02x = 0.2 + 0.03x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03x' to each side of the equation. 0.1 + -0.02x + -0.03x = 0.2 + 0.03x + -0.03x Combine like terms: -0.02x + -0.03x = -0.05x 0.1 + -0.05x = 0.2 + 0.03x + -0.03x Combine like terms: 0.03x + -0.03x = 0.00 0.1 + -0.05x = 0.2 + 0.00 0.1 + -0.05x = 0.2 Add '-0.1' to each side of the equation. 0.1 + -0.1 + -0.05x = 0.2 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + -0.05x = 0.2 + -0.1 -0.05x = 0.2 + -0.1 Combine like terms: 0.2 + -0.1 = 0.1 -0.05x = 0.1 Divide each side by '-0.05'. x = -2 Simplifying x = -2
| (6x^2-31x+18)/(2x-9) | | x-7.85=6.83 | | 10=-2/7u | | 3x^2+6-7=0 | | 133/5/24 | | y+5/6=7(1/4) | | 1.8=(7.5-x)*3 | | 262=211-y | | -3=w-2 | | (y+3)(y+3)=36 | | 7x-9=4x-6 | | -(6w+v)-4(v-3w)= | | 7x+3=5x+19 | | 10/40-20/x | | 8/15=n/6 | | x=y/4(21-z) | | 1.25x+6=.62x | | 4/x=26 | | 17+.13x=.17x | | (2x-8)(2x+8)=55 | | 51.98+.17x=55.98+.13x | | 15+.09x=10+.13x | | 6y+13=61 | | 24vx^4+12v^6w^2x=0 | | 1quatre=3 | | 3t+2x=11 | | 10(2x-5)-6= | | 0.775= | | 8(6-k)+5=-5(k-2)-5 | | ((3+8)/(9-3))/(5/6)+(4/5) | | 9.8m-20=-2m | | 11t-10=4t-5 |